A COMPREHENSIVE RESEARCH ON CULTURED MEAT: INVESTIGATION OF TURKISH PEOPLE'S PERSPECTIVES, WILLINGNESS AND ACCEPTANCE POTENTIAL TOWARDS CULTURED MEAT (Third Sector Social Economic Review, 2024)
Cultured meat production is a technological method developed in recent years to produce animal protein without traditional livestock farming. This study aims to reveal the acceptance of cultured meat, which is currently under scientific research and planned to be launched soon among Turkish consumers. Three main hypotheses were developed to determine the perspectives of Turkish consumers towards this product and to analyze the relationship between consumers' sociodemographic characteristics, concerns about cultured meat, and their intention to try it. Surveys were conducted in seven different provinces in Türkiye, where population density, industrialization, and livestock farming are prominent. The results showed that 30.1% of respondents indicated they would (definitely or probably) try cultured meat if it were to be marketed in Türkiye, while only 9% reported having no concerns about the product. The concerns about the product were identified as health reasons, distrust in new products, religious beliefs, nutritional quality of the product, extinction of livestock, and disruption of the ecological balance. Among the alternative names that could be used for the product, 46.9% of participants preferred the term ""artificial meat,"" while the word cloud analysis highlighted terms such as ""artificial,"" ""laboratory meat,"" ""unnatural,"" and ""distrust.""
Keywords: Consumer attitudes; cultured meat; food neophobia; meat consumption habits; Türkiye